Leadership style and the employee stress level at workplace - Choi, Mui Fong (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study aims to determine the relationship between leadership style and employee stress level at workplace. In this study, questionnaires were used to obtain the information and data from the respondent. This study was conducted at three branches of bank which is located at Kuching, Sarawak. A total Of 56 workers from three branches of bank were randomly chosen as the sample %)r this study, The data collected was analysed by using SPSS Version 20. Pearson Correlation was used to analyse the relationship between leadership . style and employee stress level at workplace. The finding shows that there is a relationship between autocratic leadership style and employee stress level at workplace. The strength of the relationship is weak due to r=0.461, p=0.002. Meanwhile, the findings show that democratic leadership and transformational leadership has no relationship with the employee stress level at workplace. This study proved that autocratic leadership has influence on the employee stress level at workplace.